Lizardo Pérez and Avelino Siñani, precursors of indigenous liberation. Warisata and the Parliament of the Amautas (2023)
Objective: To learn about the pedagogical project of indigenous and peasant education of Elizardo Pérez and Avelino Siñani, founders of the "Ayllu School" of Warisata in Bolivia. Originality/Contribution: we carried out a comprehensive review and systematization of primary and secondary sources of an unknown subject in the history of Latin American pedagogy. By making visible one of the first intercultural pedagogical experiences in Bolivia, we seek to raise awareness among educators, who work in territories with high indigenous density. Method: qualitative approach based on a hermeneutic paradigm and descriptive scope. The design corresponds to a bibliographic review based on the triangulation of different sources. Strategies/Data collection: Information is transformed into data, and data into knowledge through the filing of letters, archival documents, photographs, books, digital press, television documentaries and indexed scientific articles. The analysis is qualitative in nature. Conclusions: The "Ayllu School" of Warisata emerged in the context of a struggle of very unequal antagonistic social and political forces between the latifundista class and the indigenous peoples. Elizardo Pérez and Avelino Siñani were referents of indigenous and intercultural education in Bolivia, Latin America and the Caribbean. They were a paradigm of indigenous communitarianism, reciprocity and the ethos of Aymara wisdom.